Links between adolescents’ subjective health assessment, type of physical activity and posture - Daiva Mockevičienė; Lina Miliūnienė; Ilona Dobrovolskytė; Renata Žukauskaitė (Social Welfare: Interdisciplinary Approach)
Schooling period is particularly important for posture formation because during this period pupils grow and develop quickly, bones and their commissures are intensively forming. The child should also get knowledge about hygiene and healthy lifestyle but still more significance is attached to physical exercises, active physical activities, strengthening all body muscles. 60 eighth form pupils at the age from 13 to 14 years participated in the research. The majority of adolescents choose more than one kind of physical activity but physical education lessons remain the main occupation during which children engage in physical activities. More than a half of adolescents do exercises on their own, less than a half of them go to workouts or the sports club.